Noncardiovascular Disease and Critical Care Delivery in a Contemporary Cardiac and Medical Intensive Care Unit. (July 2019) - Goldfarb, Michael; van Diepen, Sean; Liszkowski, Mark; Jentzer, Jacob C.; Pedraza, Isabel; Cercek, Bojan
Background: Noncardiovascular comorbidities and critical illness are increasing in cardiovascular intensive care units (CICUs). There are limited data comparing critical care delivery, resource utilization, and costs between contemporary CICUs and medical intensive care units (MICUs). Methods: All CICU (n = 6967; 22 748 patient-days) and MICU (n = 10 892; 39 211 patient-days) admissions to Cedars-Sinai Medical Center, a tertiary care academic medical center, between January 2011 and December 2016 were reviewed. Both the CICU and MICU admitted patients for primary cardiovascular or medical conditions during the study period, but not for postoperative surgical care. Results: Patients admitted to the CICU were more frequently older, male, and had more preexisting cardiac disease ( P < .0001). More than one-fifth (21.4%) of CICU patients had a noncardiovascular primary admission diagnosis, compared to 89.2% of MICU patients. Cardiovascular intensive care unit patients had lower Acute Physiology and Chronic Health Evaluation III scores (51.1 [19.9] vs 61.1 [24.9], P < .0001) and shorter median hospital length of stay ( P < .001), but not in-unit stay, as compared to MICU patients. Mechanical ventilation, vasopressors, inotropes, renal replacement therapy, and/or blood transfusion were required in 35.0% of CICU patients compared with 62.2% of MICU patients ( P < .0001). The unit mortality rate was lower for CICU than MICU patients (4.8% vs 13.0%, P < .0001), as was the hospital mortality rate (9.3% vs 21.6%, P < .0001). The standardized mortality ratio was 0.73 for the CICU and 0.86 for the MICU. There was no difference in the mean direct cost of care per patient-day between the CICU and MICU (4011 USD [376] vs 3990 USD [214], P = .77). Conclusions: The burden of noncardiovascular diseases and the requirement for critical care therapies are high in contemporary CICU patients but remain lower compared to the MICU population. Our findings support the growing complexity of care in tertiary CICUs. Further studies are required to explore the association between critical care delivery and outcomes in this evolving population.